2021
DOI: 10.3389/fped.2021.710829
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Ventilation for Pediatric Hypoxic Acute Respiratory Failure Using a Simple Anesthetic Mask With 3D Printed Adaptor: A Case Report

Abstract: Non-invasive ventilation (NIV) is increasingly used in the supportive treatment of acute respiratory failure in children in the pediatric intensive care unit (PICU). However, finding an optimal fitting commercial available NIV face mask is one of the major challenges in daily practice, in particular for young children and those with specific facial features. Large air leaks and pressure-related skin injury due to suboptimal fit are important complications associated with NIV failure. Here, we describe a case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“… (A) The simple anesthetic mask (Ambu®King Mask, size 2) placed on the pediatric head model by a five-point headgear by our in-house 3D-printed quick release adaptor as previously described ( 22 ). (B) The PerforMax®, size XS, total face mask placed on the pediatric head model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… (A) The simple anesthetic mask (Ambu®King Mask, size 2) placed on the pediatric head model by a five-point headgear by our in-house 3D-printed quick release adaptor as previously described ( 22 ). (B) The PerforMax®, size XS, total face mask placed on the pediatric head model.…”
Section: Resultsmentioning
confidence: 99%
“…As we frequently observe quite large air leaks from such masks in daily clinical practice, we started to use an alternative interface: a simple, relatively cheap, anesthetic mask connected to a headgear via an in-house 3D-printed reusable quick-release adaptor. Recently, we described this interface as part of the successful NIV treatment in a 4-year-old boy with cardiofaciocutaneous syndrome and rhinovirus-associated hypoxic acute respiratory failure ( 22 ). Here, we used the pediatric head–lung model to more objectively investigate the extent of air leakage from this simple anesthetic mask during simulated pediatric NIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muller et al reported a case of the effectiveness of using an invented 3D Printed Adaptor with a simple anesthetic mask applying the same concept of a properly sealed mask. 10 Putting children on NIV support sometimes ease the handling of the patient by the nursing staff. Also, the parents will be more comfortable when dealing with their NIV‐supported kids.…”
Section: Discussionmentioning
confidence: 99%